Elevated perceived stress in university students due to the COVID -19 pandemic: Potential contributing factors in a propensity-score-matched sample - Auerswald, Sven; Koddebusch, Christine; Hermann, Christiane; Justus Liebig University Giessen (My University, 2024)
Objective: Onset of the Coronavirus Disease 2019 (COVID) pandemic has increased students' perceived burdens. The current study aimed to examine COVID-related changes and to identify potential factors that contribute to students' stress. Method: Adopting a cross-sectional cohort-study design, we examined perceived stress and depressive and anxiety symptoms with a specific focus on the role of study-related variables such as perceived study-related demands, study-related resources, academic procrastination, and stress-enhancing beliefs. Two cohorts (Npre-COVID = 2,175; NCOVID = 959) were recruited at the same university and matched with regard to their propensity score (age, gender, semester). Results: Compared with the pre-COVID cohort, university students in the COVID cohort reported more perceived stress, more depressive and anxiety symptoms, more academic procrastination due to fear of failure, more stress-enhancing beliefs, more distress due to the housing situation, and more perceived study-related challenges (Cohen's d = 0.15–0.45). A stepwise regression analysis identified depressive symptoms, procrastination due to fear of failure, general self-efficacy, increased study demands, perceived difficulties with self-organized learning, distress due to housing, and stress-enhancing beliefs as predictors of perceived stress in the COVID cohort. Discussion: Findings suggest that the switch to online-only education increased the study-related burden for students, primarily due to exams being replaced by a greater amount of regular coursework and imposing demands on self-organized learning. Possibly, stress-enhancing beliefs and procrastination due to fear of failure might have been elevated due to less opportunity for social referencing and lack of felt social support by peer students. Conclusion: Experienced increased burden in students during the COVID pandemic was mostly accounted for by a lack of perceived individual resources rather than by an increase in objective study-related demands.
Keywords: ddc:150